Network structure of gelatin gel at high pressure determined by rheological measurements - Kulisiewicz, Leszek; Delgado, Antonio (High Pressure Research, 2009)
The present paper reports on rheological investigations of gelatin gels cured under high-pressure conditions. Measurement of the storage modulus showed that gels developed under elevated pressure revealed higher values of G' in comparison to gels cured at ambient pressure. Based on the kinetic theory of rubber elasticity, it is presumed that the higher values of the storage modulus originate from the increased number of triple helix junction zones per molecular chain. Additionally, considering the triple helix nucleation process, it is hypothesised that the average length of the triple helix junction zones is lower, at least in the initial period of gel network building, if the gel is setting at high pressure.
UnivIS-Import:2015-03-09:Pub.2009.tech.ITC.stmmec.networ
Keywords: Biopolymer; Gelatin; High pressure; Molecular structure; Rheology